EDUCATIONAL ACHIEVEMENTS OF THE FIRST YEAR STUDENTS OF MIDWIFERY: EIGHT-YEAR OF ADMISSION VALIDITY STUDY FOR STUDIES OF THE 1ST DEGREE. - Panczyk, Mariusz; Belowska, Jarosława; Zarzeka, Aleksander; Gotlib, Joanna (Polish Nursing / Pielegniarstwo Polskie, 2016)
Aim. Assessment of predictive validity of the selected socio-demographic factors and admission criteria for the candidates of full-time studies of the 1st degree at the department of Midwifery at the Medical University of Warsaw (MLW) between the years 2005/06 and 2012/13. Material and methods. Data of 703 students of Midwifery concerning grades achieved in the subjects completed with an exam in the first year of studies. The evaluated socio-demographic variables: age, place of completing high school, type of maturity exam. Admission criteria based on the results of the maturity exam in Polish language, foreign language and an additional subject. Predictive validity was assessed using the model of logistic regression and multiple function. Calculations: STATISTICA 12.5, α = 0.05. Results. For the model of logistic regression, no socio-demographic factor O'- admission criterion was of significant importance considering the probability of rot completing studies. In the model, the function of multiple regression, among many sociodemographic variables, both age and the place of completing high school were of significance considering the grade point average of a student. All three admission criteria were relevant predictors, however, the strongest one being a candidate's score in an additional subject (βstand= 0.348), followed by a foreign language and Polish language βstand 0.190 and 0.178, respectively). Conclusions. Admission criteria applied so far, present an appropriate level of prognostic validity. However, it is still necessary to adjust the admission policy so as to increase the attractiveness of Midwifery studies among the candidates.